Valgus osteotomy by external fixation for treatment for developmental coxa vara - Hefny, Hany (Springer Milan, 2013)
Valgus subtrochanteric osteotomy is the standard surgical treatment for coxa vara. Nevertheless, there is no consensus on the method of fixation and osteotomy technique. There are some reports on employing rigid internal fixation methods that preclude the need of postoperative immobilization. This is a technical description of a valgus osteotomy performed using external fixation with preoperative and postoperative data on a cohort of 9 patients. In this study, 9 hips in 9 patients with the diagnosis of developmental coxa vara underwent a subtrochanteric osteotomy with stabilization by an external fixator. The planned correction angle was obtained for all 9 patients with the osteotomies healing primarily. Radiographic analysis showed an improvement in Hilgenreiner’s epiphyseal angle and the neck-shaft angle. There were no major complications associated with use of this method of stabilization. Minimal access surgery using external fixation for a valgus osteotomy of the proximal femur is safe and effective for the treatment for coxa vara and limb length discrepancy. It has potential advantages over commonly used open techniques and provides available alternative to currently applied methods used for fixation of proximal femoral osteotomies.